ENZYMATIC RESISTANCE TO INSECTICIDES IN LARVAE OF Heliothis virescens (Lepidoptera: Noctuidae) - VALENCIA, EDISON; PLATA, CECILIA; CORREDOR, CARLOS; CARDONA, CÉSAR (Revista Colombiana de Entomología, 1993)
Heliothis virescens (Fabricius) is an important pest of several tropical crops and its control depends on the use of chemical insecticides in a very narrow way. This insect shows a big capacity for the development of resistance, mainly based on metabolic mechanisms. We have determined the physiological resistance levels in larvae of H. virescens by comparison of two populations of the pest, one from the North Atlantic Coast (resistant) and the other from the Valle del Cauca (susceptible), using topical applications in vivoand test of enzymatic activity in vitro, (esterases, carboxylesterases, and Mixed Function Oxidases System, MFOs). The application was done over thírd instar larvae. The products used were: endosulfan, triazophos, methyl parathion, deltamethrin, and fenvalerate. The enzymatic extracts were obtained from fifth instar larvae, surviving to the DL 90th (n=1 to 10). For the MFOs, a group of larvae was fed with an artificial diet added sodic phenobarbital as enzymatic inducer. The activity of cytochrome P-450, esterases, and carboxylesterases was determined by spectrophotometric methods. The results for the population from the Valle del Cauca (susceptible) show: 1) A higher mortality for all the treatments. 2) A lower general activity of the MFOs. 3) A similar grade of inducibility of the MFOs in comparison to the resistant population. 4) A slightly lower average activity of esterases and carboxylesterases than the activity reported for H. virescens from the Atlantic Coast. 5) Significant variations on the activity of esterases and carboxylesterases depending on the insecticide tested. This information allows to conclude that: The MFOs, as one of the resistance mechanism, is more efficient in the population from the Atlantic Coast and the grade of inducibility of this system is similar for both populations. This shows that H. virescens from the Valle del Cauca are genetically able to develop resistance, although this population has at present, a normal susceptibility as a result of the rational use of chemical insecticides. With respect to the esterases and carboxylesterases activity, it is accepted that these molecular behavior patterns could be the result of the management and selection pressure-related to commercial applications, already done before the collection of the insects from the field, belonging to each one of the colonies under this study.